(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
This article presents the results of testing a collection of tomatoes of foreign and local selection in film unheated greenhouses. Testing of tomato varieties in film greenhouses showed that many promising samples are a valuable source material for creating early-ripening, highly productive and high-tasting disease-resistant tomato fruits